Hipertensos diabéticos e o risco de doenças cardiovasculares: uma coorte histórica - Sousa, Andréa Cristina de (2016)
Background: Diabetic patients are at increased risk of cardiovascular disease and mortality, reducing the life expectancy of 5 to 15 years. Type 2 diabetes is an increased risk especially from 4.9 times to cardiovascular mortality. When hypertension is combined with diabetes or risk of suffering a cardiovascular disease is even greater. Objective: To identify non-lethal cardiovascular outcomes and indicative of decrease of kidney function in a cohort of diabetic and non-diabetic hypertensive type 2 in regular and continuous treatment in a specialized center for hypertensive patients Design and methods: Historical cohort of diabetic hypertensive (exposed group) and nondiabetic (unexposed group) in regular treatment for at least 11 years in a reference center for hypertension treatment. Initial cohort assessment in 2004, with intermediate follow-up in 2009 and final follow-up in 2015; variables studied: gender, race, age, blood pressure, body mass index (BMI), glycated hemoglobin, duration of hypertension diagnosis, diabetes and specialized treatment, non-fatal cardiovascular events, indicative of decrease in renal function using creatinine clearance. For blood pressure control among non diabetics values of <140/90mmHg were considered and for diabetics values of <130/ 80mmHg (strict goals) and <140/90mmHg (overall goal) were considered. For the variables association analysis was used chi-square, test Fisher's exact and Relative risk at a 5% significance level. Results: Included 139 hypertensive patients (diabetics: 55; nondiabetic: 84), with a mean time of hypertension treatment at the first analisis of 5.8 years. Most patients were females (75.5%) and the white race was predominant (55.8%). At the beginning the group of diabetic hypertensive patients had higher frequency of obesity (45.5%), and also uncontrolled blood pressure. The lack of blood pressure control was not associated with any other variable. At the final evaluation, 85.2% of the exposed group was using 3 or more antihypertensives, whereas in the unexposed group to the proportion was 45.2% (p <0.001). In eleven years, the exposed group had a higher risk of being affected by acute myocardial infarction (12.2 times) (RR 12,2 CI95% 1,6 – 95,0); stroke (6.1 times more) (RR 6,1 CI95% 1,3 – 27,7); and hospital admissions (2.2 times) hospitalizações (RR 2,2 IC 95% 1,6 – 3,0); compared to the unexposed. The diabetes diagnosis time in this cohort was not associated with the incidence of the analyzed events. Also the exposed group had 2.3 times greater risk to not controll the blood pressure. Regarding kidney function the exposed group decreased more significantly creatinine clearance. They started with 82,9 min/1.73m2 and finished with 64,2 min/1.73m2 and the unexposed group began with 70,2 min/1.73m2 and finished 61,9min /1.73m2 (p <0.05). However, this fact did not contribute to hypertensive diabetics had higher loss of kidney function, because in the end they had renal injury rates of 43.4% and non-diabetic patients 45.2% (p> 0.05). Conclusion: Diabetics had lower blood pressure control rates over the cohort, despite being assisted at a specialized service. They were more obese and ultimately used more antihypertensive than non-diabetics. Hypertensive diabetics had higher chance to be affected by cardiovascular outcomes compared to non-diabetic patients in this cohort.